Invention and International Diffusion of Water Conservation and Availability Technologies Evidence from Patent Data - Dechezleprêtre, Antoine (OECD Publishing, 2015)
This paper identifies over 50 000 patents filed worldwide in various water-related adaptation technologies between 1990 and 2010, distinguishing between those related to water availability (supply) and water conservation (demand) technologies. The paper then analyses the innovation activity - including inventive activity by country and technology, international collaboration in technology development, and international diffusion of such water-related technologies. The results suggest that although innovation activity in water-related technologies has been increasing over the last two decades, this growth has been disproportionately concentrated on supply-side technologies. Moreover, most innovation worldwide occurs in countries with low or moderate vulnerability towards water scarcity. While this is a reflection of the fact that most developed economies do not face severe water stress, this result highlights the importance of international technology transfer and policies that facilitate broad diffusion of these technologies in water-stressed countries
Keywords: Environment; Science and Technology